PENGARUH PENERIMAAN PAJAK KENDARAAN BERMOTOR DAN PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI DKI JAKARTA TAHUN 2018-2022 - Laia, Lisapna; Irawan, ade; sagitarius, Elda (JURNAL ILMIAH EDUNOMIKA, 2024)
Abst Regional Tax Law no. 34 of 2000 states that taxes are mandatory contributions to society by individuals or legal entities that are not balanced by direct consideration, can be imposed based on applicable laws and regulations, and are used to finance the administration of regional government. This research aims to determine the relationship between the effects of taxes motorized vehicles with parking tax on local revenue (PAD) in DKI Jakarta 2018-2022. The research design used to compile this research is a quantitative research design that describes the relationship between the variables studied and analyzes them by testing hypotheses. Based on the discussion above, it can be concluded that motor vehicle tax revenue and central parking tax fill the regional treasury of DKI Jakarta. Sustainability and increased efficiency in the use of these resources can have a positive impact on development and public services in the future. As time goes by, continuous monitoring of policies and community responses becomes key in maintaining the sustainability and balance of this PAD revenue system.